Fractales en Arqueología: aplicación en la pintura rupestre de sitios del México prehispánico. - Aline Lara Galicia (Virtual Archaeology Review)
This study exposed analysis fractal by the dimension D in the rock art. The Fractals is a new tool in the software application and digital photography for the recognition of raw materials, the study of its form, degradation, specific parts of paint, and providing new data the virtual reconstruction. The analyzes focus on various pictorial sets of the region Mezquital Valley, Hidalgo, Mexico; region where are concentrated more than 100 caves, comparing 74 images to analyze the various pictorial traditions. The structure fractal describes the dimension of the represented objects, not only according to its space where the figure is placed, but the possibility of being a fraction in which all the surfaces can be observed (rock, paint).